Damage by baboons to pine plantations in South Africa : with special reference to the ecology of three troops of baboons in the Western Cape - Erasmus, Diane (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.